Cultural appropriation in fashion and entertainment - Kawamura, Yuniya, 1963-; De Jong, Jung-Whan Marc (London ; New York : Bloomsbury Visual Arts, 2022)
"Unpicks the knotty problem of cultural appropriation in fashion and entertainment, using sociological analysis to explore international examples and engage with the passionate debates that surround them as well as the implications for designers, artists and consumers" (Provided by publisher.)
Introduction-Culture -- Academic studies on cultural appropriation -- Fashion -- Entertainment -- Ambivalance and paradox.
boek